Research on the Reconstruction of Human Resource Strategy Based on Digital Transformation - Jiang, Huihui (Education Insights, 2026)
With the rapid advancement and widespread adoption of digital technologies, digital transformation has emerged as a critical pathway for enterprises to enhance competitiveness and achieve sustainable development. This study examines the restructuring of corporate human resource strategies within the context of digital transformation. Through systematic analysis of relevant data, it investigates the challenges and opportunities that digital transformation introduces to human resource management practices. The findings indicate that existing human resource strategies in enterprises undergoing digital transformation exhibit multiple deficiencies, making comprehensive strategic restructuring both necessary and urgent. By employing real-world data to construct two comparative data tables, this paper visually and quantitatively illustrates changes in key performance indicators (KPIs) in human resource management before and after digital transformation initiatives. These empirical observations provide persuasive evidence supporting the need for strategic realignment and offer targeted reconstruction approaches aimed at improving organizational adaptability, workforce capability, and long-term sustainability. The study ultimately delivers practical and actionable insights to guide enterprises in optimizing human resource strategies and maintaining sustainable development in the digital era.